Integration of Character Education and Tazkiyah al-Nafs: Perspective of Abū Hasan al-Nadwī - Mulyadi Mulyadi (LPPM IAIN Kudus, 2021)
This article aims to analyze Ab Hasan al-Nadwī’s thoughts on tazkiyah al-nafs. Then, the character values in tazkiyah al-nafs are integrated into the concept of character formulated by the Ministry of Education.The concept of character by the Ministry of Education has a clear nationalism vision but has no technical direction. Then it can be filled with tazkiyah al-nafs by Abū Hasan al-Nadwī who has technical directions. The integration of the concept of character by the Ministry of Education and tazkiyah al-nafs by Abū Hasan al-Nadwī is useful for producing a character concept that has technical direction and has a nationalism vision. The research method used is integration-interconnection. Eighteen character values by the Ministry of Education are filled with tazkiyah al-nafs by Abū Hasan al-Nadwī which includes fiqh dhahir and fiqh bathin. The research findings produce tazkiyah al-nafs which includes shalat, fasting, zakat, sunnah worship, ‘ibadah bathin integrative with eighteen character concepts which include religious, honest, tolerant, discipline, active, creative, independent, democratic, curios, nationalist, patriotic, appreciative, friendship, peaceful, literative, environmentalist, humanist, and responsibilities.